Alteration of brain and interrenal StAR protein, P450scc, and Cyp11beta mRNA levels in atlantic salmon after nominal waterborne exposure to the synthetic pharmaceutical estrogen ethynylestradiol - Lyssimachou, Angeliki; Arukwe, Augustine (Journal of toxicology and environmental health. Part A, 2007)
Pharmaceuticals are ubiquitous pollutants in the aquatic environment, where their potential effects on nontarget species like fish has only recently become subject of systematic investigations. Recently, it was shown that the documented xenoestrogen nonylphenol produced variations in brain steroidogenic acute regulatory (StAR) protein, cytochrome P-450-mediated cholesterol side-chain cleavage (P450scc), and cytochrome P-45011beta hydroxylase (CYP11beta) gene transcripts of exposed juvenile salmon (Arukwe, 2005). In the present study, experiments were undertaken to examine the effect of the synthetic pharmaceutical endocrine disruptor ethynylestradiol (EE2), given in water at 5 or 50 ng/L and sampled at d 0 (control), 3, and 7 after exposure, on these key and rate-limiting brain and interrenal steroidogenic pathways of juvenile salmon using quantitative (real-time) polymerase chain reaction (qPCR). Our data, which are based on nominal exposure concentrations, show that brain and head kidney StAR and P450scc expression were modulated by EE2 in a time- and concentration-specific manner. While the StAR protein and P450scc showed EE2 concentration-dependent transcriptional increases in the brain and head kidney at d 3 after exposure, no significant effect was observed at d 7. The EE2 induced effects at d 7 were underscored because the carrier solvent (dimethyl sulfoxide, DMSO) produced significant induction of the StAR protein and P450scc in both the brain and head kidney at d 7 compared to d 3 postexposure. CYP11beta transcript was detected in the brain and head kidney, where the expression patterns were modulated by EE2 in a concentration-and time-specific manner. In the brain, DMSO produced significant changes in the CYP11beta gene expression at d 7 compared to d 3 after exposure. These changes in the levels of StAR, P450scc, and CYP11beta mRNA levels in important steroidogenic organs suggest that the experimental animals are experiencing a time-dependent impaired steroidogenesis. Thus, the StAR protein, P450scc, and CYP11beta might represent sensitive diagnostic tools for short-term and acute exposure to endocrine disrupting chemicals. In view of the present study and high concentrations of EE2 reported in effluents and surface waters from Europe and the United States, pharmaceuticals in the environment represent potentially more serious health concern both to humans and wildlife than earlier anticipated.